Evaluation of Learner Autonomy in the Algerian Third Year Secondary School Textbook ‘New Prospects’ - Mezhoud, Soraya (Journal of Human Sciences, 2020)
This paper evaluates the Algerian third year secondary school textbook ‘New Prospects’ to discover to what extent its content promotes learner autonomy. New Prospects was designed in compliance with the principles of the Competency Based Approach that aim at producing learners who are competent not only inside the classroom but also in their everyday lives outside of the school by promoting responsibility and autonomy in them. The hypothesis on which the paper is based is that if New Prospects complies to the principles of learner autonomy as stipulated in the CBA it will manage to produce autonomous learners. The methodology adopted in this paper consists of an evaluation checklist elaborated on the basis of the principles constituting autonomous learning identified in the literature review herein. The results obtained indicate that ‘New Prospects’ largely complies to these principles.